If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 3 = 4y + 5y Reorder the terms: 3 + 8y = 4y + 5y Combine like terms: 4y + 5y = 9y 3 + 8y = 9y Solving 3 + 8y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 3 + 8y + -9y = 9y + -9y Combine like terms: 8y + -9y = -1y 3 + -1y = 9y + -9y Combine like terms: 9y + -9y = 0 3 + -1y = 0 Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| y=-3(x-7)*2+5 | | -3(3x-5)-3(4x+4)= | | 90+2x-16=180 | | 3(5x-2)-3(x+4)= | | 12-(-7)-8= | | -0.2x-0.6=1.2x-0.83 | | 2.3=4.1+y | | -.2k=-15 | | -12n+15=-15-10n | | 2(7-y)=2y+11 | | 2x+15=x+5 | | 24overh=6 | | -13r+10=-4r+19-8r | | (5x-2)+2(x-1)= | | 57=w/3 | | 4(w-2)-w=46 | | sqrtx^4+18x^3+6=3 | | 4x/4=-13/4 | | -(2x-4)-4(x+5)= | | 7x-4=4(x-3) | | 0x=-13 | | 4y+xy+6x+(x*x)+8=z | | 28x+9=9x+41 | | -2(5x+4)-5(4x-3)= | | 10+10k=4k-10-10 | | 100/365 | | -5(2x+3)-(2x+1)= | | (10s^5)(7st^4)= | | 7-(3+5)= | | -1+7u=-10+10u | | -2(4x-3)+5(2x-1)= | | y/-8=10 |